Rekonstruksi Pengaturan Hak Advokat dalam Pendampingan Hukum Terhadap Klien pada Tahap Pemeriksaan di Kepolisian dalam Perspektif Negara Hukum dan Hak Asasi Manusia. - Ba’arrffan, Saaqib Faiz; Heliany, Ina; Hasan, Bob (LITERATUS, 2025)
This journal critically examines the regulation of advocates' rights in legal assistance to suspects during the investigation stage by comparing the Old Criminal Procedure Code (Law No. 8 of 1981) and the Newest National Criminal Procedure Code. The main focus of the analysis is directed at the extent to which these normative changes are in line with the principles of the rule of law, the protection of human rights, and the principle of fair trial. The research method used is normative juridical with a statutory, conceptual, and comparative approach. The results of the study indicate that although the Newest National Criminal Procedure Code normatively expands the recognition of advocates' rights, it still leaves doctrinal problems in the form of normative ambiguity and proceduralist tendencies. Therefore, this Thesis Research offers a progressive reconstruction of the regulation of advocates' rights that positions advocates as guardians of the suspects' constitutional rights from the early stages of the criminal justice process.